STRATEGI CO BRANDING OREO DENGAN SUPREME - Albertus Sudarmanto; Jesaya Ginting; Veronika Sari Prihandayani; Wilogo Siwi Pamungkas (Marketgram Journal, 2023)
Competition in the business world is getting tougher causing business actors to be required to have a competitive advantage in order to be able to compete in the market. One of the strategies carried out by the company is Co-branding or Collaboration Branding or merging brands. Co-branding is a collaboration format between two or more brands that already have significant recognition in their market. And the products produced from this co-branding are unique, unusual, even co-branding products are usually sold in limited editions. One form of product resulting from the Co-branding is Oreo with Supreme. This co-branding is a collaboration between the Supreme brand, which is basically a fashion brand, and Oreo, which is basically a food product brand. This journal reviews the Co-branding between Oreo and Supreme using a descriptive qualitative research approach. And shows that the Co-branding strategy carried out by Oreo Supreme produces premium new products and has a significant influence in the business world.